Enhanced Protocatechuic Acid Production From Glucose Using Pseudomonas putida 3-Dehydroshikimate Dehydratase Expressed in a Phenylalanine-Overproducing Mutant of Escherichia coli - Örn, Oliver Englund; Sacchetto, Stefano; van Niel, Ed W. J.; Hatti-Kaul, Rajni (Frontiers in Bioengineering and Biotechnology, 2021)
Protocatechuic acid (PCA) is a strong antioxidant and is also a potential platform for polymer building blocks like vanillic acid, vanillin, muconic acid, and adipic acid. This report presents a study on PCA production from glucose via the shikimate pathway precursor 3-dehydroshikimate by heterologous expression of a gene encoding 3-dehydroshikimate dehydratase in Escherichia coli. The phenylalanine overproducing E. coli strain, engineered to relieve the allosteric inhibition of 3-deoxy-7-phosphoheptulonate synthase by the aromatic amino acids, was shown to give a higher yield of PCA than the unmodified strain under aerobic conditions. Highest PCA yield of 18 mol% per mol glucose and concentration of 4.2 g/L was obtained at a productivity of 0.079 g/L/h during cultivation in fed-batch mode using a feed of glucose and ammonium salt. Acetate was formed as a major side-product indicating a shift to catabolic metabolism as a result of feedback inhibition of the enzymes including 3-dehydroshikimate dehydratase by PCA when reaching a critical concentration. Indirect measurement of proton motive force by flow cytometry revealed no membrane damage of the cells by PCA, which was thus ruled out as a cause for affecting PCA formation.